2021
DOI: 10.3390/molecules26237123
|View full text |Cite
|
Sign up to set email alerts
|

From Adsorbent to Photocatalyst: The Sensitization Effect of SnO2 Surface towards Dye Photodecomposition

Abstract: Semiconductor photocatalysis is considered one of the most promising technologies for water purification from toxic organic dyes. However, to reliably evaluate the possibility of using a given material as a photocatalyst, it is crucial to investigate not only the photocatalytic activity but also its affinity towards various dyes and reusability. In this work, we studied the adsorptive/photocatalytic properties of hollow-spherical raspberry-like SnO2 and its SnO2/SnS2 heterostructures that were obtained via a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…the adsorption for RS with RS_1:1, represented by violet and green dashed lines in Figure a, respectively). The observed effect of pronounced NBT adsorption on the SnO 2 surface is consistent with our previous study, which revealed that the bare SnO 2 - and SnS 2 -coated samples exhibit different adsorption properties. It turned out that the RS sample more favorably adsorbs cationic dyes, such as rhodamine B (NBT is also a cationic dye).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…the adsorption for RS with RS_1:1, represented by violet and green dashed lines in Figure a, respectively). The observed effect of pronounced NBT adsorption on the SnO 2 surface is consistent with our previous study, which revealed that the bare SnO 2 - and SnS 2 -coated samples exhibit different adsorption properties. It turned out that the RS sample more favorably adsorbs cationic dyes, such as rhodamine B (NBT is also a cationic dye).…”
Section: Resultssupporting
confidence: 92%
“…Based on the conducted experiments, IC was chosen as a representative model dye for photocatalytic tests. These tests showed that increasing SnS 2 content in the samples improves the photodegradation rate of IC (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, TMCh were associated mainly with thermoelectric applications and are still considered to be the benchmark for other materials, displaying performance beyond the capabilities of other materials groups. [1][2][3][4][5][6][7][8][9][10] However, recently, they have gained a lot of interest with regard to the possibility of their utilization in a number of other technologies operating on the basis of electrocatalytic processes, including photochemistry, [11][12][13] sensors, 12,14,15 fuel cells, and catalysis. 12,16,17 This interest stems from their excellent catalytic activity with respect to some of the most fundamental catalytic reactions, namely hydrogen evolution reaction (HER), and the oxygen evolution reaction (OER).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the potential toxicity and harmful effects of indigo carmine on the ecosystem and biodiversity, its presence and concentration must be reliably determined. Different methods have been proposed to identify and quantify indigo carmine in wide-range samples, based mainly on UV/Vis spectrometry [ 14 , 15 , 16 , 17 , 18 ], electrochemical techniques [ 19 , 20 , 21 ], chromatography [ 22 , 23 , 24 ], FTIR spectroscopy [ 12 , 25 ], as well as advanced digital imaging techniques [ 26 , 27 ]. Understandably, all of these techniques have different sensitivity and accuracy of indigo carmine detection mainly depending on sample nature (to be more precise on its matrix).…”
Section: Introductionmentioning
confidence: 99%